Exploring the Implementation Challenges and Achievements of the 2016 Civil Service Law in Egypt: A Study - Tarek, Nahla (AUC Knowledge Fountain, 2023)
The American University in Cairo School of Global Affairs and Public Policy Department of Public Policy and Administration